A Central Clearing Clinic to Provide Mental Health Services for Refugees in Germany - Bajbouj, Malek; Panneck, Patricia; Winter, Sibylle-Maria; Ajami, Carlos; Alabdullah, Jihad; Benedikt Burger, Max; Haberlandner, Anja; Hahn, Eric; Heinz, Andreas; Heuser, Isabella; Hoyer, Armin; Kluge, Ulrike; et al. (Frontiers in Public Health, 2021)
Objective: To determine migration related distress pattern in refugees and feasibility of a de novo established, central low-threshold outpatient clinic serving more than 80·000 newly arrived refugees in the metropole of Berlin. Methods: In an observational cohort study the relative prevalence of major psychiatric disorders by age, place of living within Berlin, language and region of origin were assessed in a refugee cohort from 63 nationalities speaking 36 languages. Findings: Within 72 months, a total of 3·098 cases with a mean age of 29·7 years (11·7) have been referred from all 12 districts and 165 of 182 subdistricts of Berlin to the CCC. 33·7% of the patients were female. The three most frequent diagnoses were unipolar depression (40·4%), posttraumatic stress disorder (24·3%), and adjustment disorder (19·6%). Conclusion: The present data gives insight into the distribution of mental disorders in a large sample of refugees and provides evidence that a CCC is an effective service to quickly and broadly provide psychiatric consultations and thus to overcome classical barriers refugees usually experience in the host communities. In Berlin, Germany, and Europe treatment resources for this population should focus on stress and trauma related disorders. Funding: The Central Clearing Clinic was funded by the State of Berlin.